TEKNOLOGI ASSISTIVE SEBAGAI MEDIA PEMBELAJARAN SISWA AUTISME DI SLB DHARMA WANITA PANE KOTA BIMA - Indriani, Irma; Aminullah, Aminullah (Fitrah, 2024)
This research aims to analyze the implementation of assistive technology as a learning medium for autistic students at Sekolah Luar Biasa (SLB) Dharma Wanita Pane in Bima City. The subjects of the study are the school principal and teachers. The research employs a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. Interviews are used to gather direct information from the principal and teachers at SLB Dharma Wanita Pane about the use of assistive technology in the learning process. The results of the study indicate that SLB Dharma Wanita Pane has implemented low-tech assistive technologies in teaching, such as visual and audiovisual technologies like images and animation videos, which refer to simple tools or devices that do not require advanced technology. This implementation has had both positive and negative effects on the students at SLB Dharma Wanita, particularly on autistic students. The researcher also identified several challenges, such as limited internet access and teachers' technology skills. Therefore, the study recommends that the government and schools improve technological infrastructure and provide training for teachers to effectively utilize assistive technology.